Redirecting patients from the pediatric emergency department to community locations for care: A qualitative study of healthcare professional and leader perspectives - Erica Qureshi; Quynh Doan; Jessica Moe; Steven P. Miller; Garth Meckler; Brett Burstein; Jehannine (J9) Austin (PLoS ONE, 2025)
Objectives Emergency department (ED) to community (ED2C) programs, which redirect patients from the pediatric ED to community healthcare professionals represent a promising strategy to reduce the impact of non-urgent visits on the pediatric ED. Given an ED2C program’s potential impact on various care professionals, we completed a qualitative study to explore key informants’ attitudes and perceptions of pediatric ED2C programs. Methods We conducted one-on-one semi-structured interviews with key informants in British Columbia, Canada. Participants included: pediatric ED staff – triage nurses and physicians; community professionals – pediatricians and family physicians; and health system leaders responsible for pediatric and emergency care in British Columbia. Interviews were recorded, transcribed verbatim, de-identified, and analyzed using reflexive thematic analysis within an interpretive description framework. A visual model was developed to depict key themes in attitudes and perceptions towards pediatric ED2C programs. Results We interviewed 24 participants: 6 community professionals, 11 pediatric ED professionals, and 7 healthcare leaders. Participants viewed the ED2C program as a valuable solution to address pediatric system strain provided that systemic barriers are addressed, and both emergency and community settings are equipped with adequate training and resources. Participants emphasized the need for clear guidelines on eligibility and operations to build confidence and enhance program effectiveness. Conclusions Our findings suggest there is support for ED2C programs as a means to reduce the impact of non-urgent pediatric ED visits and strengthen community-based care. Successful implementation will require coordinated planning, resource investment, and clear operational frameworks.